Institutional Framework for Human Rights Protection in Americas: The Inter-American Court of Human Rights - Hassanová, Rebecca Lilla (Regional Human Rights Protection Systems Outside Europe, 2026)
The next chapter is devoted to the analysis of the institutional framework of human rights protection in Americas, concretely to the Inter-American Court of Human Rights. It aims to present its legal background, its position within the Inter-American regional human rights system and its relationship with the most influential actors, such as the Inter-American Commission. The research in the first half of the work examines the aspects of the contentious jurisdiction and advisory jurisdiction. Through these subchapters the author explains the methods and the modus operandi of the procedures before the Court. The analysis of individual petitions presents the most influential and effective means of the system. Furthermore, the work, via the advisory jurisdiction, presents the nature and the position of the Court in the system, as well as the most significant principles governing the Inter-American human rights framework. The following final part explores the criteria of admissibility which are fundamental for establishing the jurisdiction of the Court.Keywords: Inter-American human rights system, Inter-American Court of Human Rights, Inter-American Commission, contentious jurisdiction, advisory opinion